Agroecologia e juventude camponesa: o caso da Comunidade de Resistência Emiliano Zapata em Ponta Grossa/PR - Taques , Welington Cesar (2016)
The countryside and the peasants besides producing food are also producers of migrants, because from the Green Revolution the countryside has undergone a population emptying, resulting from the migration of the peasants, especially young people, to the city. Peasant youth faces the problems of an agriculture subordinated to the interests of large capitalist corporations that in Brazil correspond to agribusiness. Business agriculture, agribusiness, is antagonistic to peasant agriculture. In this antagonism, the proposal of agro-ecological production, inserted in the context of peasant resistance and resistance, stands out. The MST is one of the social movements in the countryside that organizes resistance and believes in agroecology as an agricultural practice that humanizes and establishes new social and land relations beyond capitalist production relations. The Community of Resistance Emiliano Zapata is an example of this resistance. This community, located in the municipality of Ponta Grossa / PR, currently has 53 families camped and since 2003, families have organized their production based on the principles of agroecology. At the age of 13, families faced numerous difficulties to produce agroecologically. The lack of concretization of the settlement, in addition to other difficulties faced by the families encamped, made many young peasants leave the community. But because of the importance that agroecology has for peasant agriculture, it constitutes an alternative to face the difficulties experienced by the families and young people of the Community of Resistance Emiliano Zapata.